When are you taking us outside? An exploratory study of the integration of the outdoor learning in preschool and primary education in Quebec - Beauchamp, Audrey-Anne; Lacoste, Yannick; Kingsbury, Célia; Gadais, Tegwen (Frontiers in Psychology, 2022)
Introduction: Recent research investigating the benefits of being outdoors and contact with nature in children showed strong associations with children’s health and development. More teachers are choosing to integrate outdoor learning (OL) into their practice, but few studies have focused on OL in the school environment, particularly in Canada and more specifically in Quebec, despite the fact that the school context lends itself favorably to this practice. Objective: The purpose of this study was to portray OL in preschool and primary schools in Québec by identifying three key elements: 1) teachers’ perception of the outdoors, 2) the uses of OL in schools, and 3) teaching strategies and factors that influence teachers’ integration of OL. Methodology: Semi-structured group interviews (n=4) conducted with 14 teachers and participant observations (n=4) were used for data collection. Inclusion criteria were to be a preschool or primary school teacher, to have taught at least eight sessions of OL in the past year, and to have no connection or contact with the research team prior to the start of the study. Results: First, the results showed that teachers commonly understood the outdoors as being in the open air, practicing a physical activity, having the presence of nature, providing educational freedom and targeting an intention. Second, teachers appeared to incorporate a variety of pedagogical intentions in OL (e.g., interdisciplinary learning), in a variety of settings (e.g., city parks, woodlands), and with a variety of academic subjects (e.g., French, mathematics) and learning tasks (e.g., nature shelter building). Third, teachers used a wide range of teaching strategies in OL (e.g., well-established routines). Participants also identified multiple factors specific to their setting that appeared to facilitate (e.g., parental support) or limit (e.g., storage of materials) their integration of OL into the school environment. Conclusion: This study provided a better understanding of the current use of the OL in the Quebec school environment by identifying the common characteristics, limitations and winning strategies of its use in schools. Teachers and schools interested in OL could benefit from the results of this study, particularly those interested in adopting a Forest School or Udeskole approach.